Pengaruh Atmosfer Toko Dan Promosi Terhadap Impulse Buying Melalui Emosi Positif Sebagai Variabel Mediasi - Melvyn Ketcy Vannesse; Muana Nanga; Meilisa Alvita (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In business, the store atmosphere can be an important factor in influencing the emotions that consumers feel when visiting a store so that it can influence purchasing decisions, both positively and negatively. Apart from store atmosphere, promotions can also influence impulse buying and positive emotions which act as mediators between store atmosphere variables and impulse buying and promotional variables on impulse buying. This research aims to determine the effect of store atmosphere and promotions on impulse buying through positive emotions as a mediating variable with a study conducted at McDonald's Jabodetabek. Data testing using quantitative methods was obtained through questionnaires with a total of 203 respondents which were processed using SEM-PLS where the software used was SmartPLS 4 to test descriptive statistics, outer model, inner model, Cronbach's Alpha, Composite Reliability & Average Variance Extracted (AVE), and hypothesis. The results of path coefficient testing show that the store atmosphere has an insignificant influence on impulse buying, but promotions and positive emotions have a positive and significant influence on impulse buying. Meanwhile, the mediating variable, namely positive emotions, shows the store atmosphere and promotions can partially have a positive and significant influence on impulse buying.